The sacred and the sinister: studies in medieval religion and magic - Collins, David J. (The Pennsylvania State University Press, 2019)
A collection of essays focusing on the relationship between concepts of the holy and the unholy in western European medieval culture. Demonstrates how religion, magic, and science were all modes of engagement with a natural world that was understood to be divinely created and infused with mysterious power.